O25 Genome wide analysis identifies potential mechanisms of non-alcoholic fatty liver disease. (19th June 2022) - Ho, Brian; Thompson, Andrew; Jorgensen, Andrea; Pirmohamed, Munir
Abstract : Introduction: Non-alcoholic fatty liver disease (NAFLD) is a complex trait disorder. Genome-wide association studies (GWAS) of MRI hepatic image phenotypes and health records may allow identification of single nucleotide polymorphisms (SNPs) associated with NAFLD. In this study, we have used the UK Biobank to identify potential genetic risk factors for NAFLD. Method: Using available data (application ID: 53754) for hepatic MRI proton density fat fraction (PDFF) combined with clinical records, we performed GWAS for NAFLD (continuous and categorical traits) using BOLT-LMM, adjusted for age, sex, diabetes, alcohol intake, smoking status and Townsend Index. An exploratory significance threshold (p < 5x10 -6 ) was used. Clumping, annotation, expression quantitative trait loci (eQTL) analysis with genome tissue expression database and gene-pathway analysis was performed on the Functional Annotation of Genome Wide Association Study Platform. Lastly, phenome wide association study was performed on UK Biobank traits on lead SNPs (r 2 < 0.1) was searched for on GeneAtlas. Post-GWAS associations were corrected for a FDR < 0.05. Results: We identified 32 and 24 lead SNPs (r 2 < 0.1) in continuous and categorical NAFLD trait GWAS, respectively. Independent SNPs (r 2 < 0.6) within these loci replicated previously published SNPs associated with NAFLD ( PNPLA3, TM6SF2, MBOAT-TMC4, APOE, GATA2DA, ZNF101, PBX4 and PARVB) . We identified 29 potential new variants in or near genes related to autophagy and inflammation ( AMBRA1, SND1 and NFATC1 ), cell cycle and transcriptional/protein regulation ( KBTBD12, ADCY8, CSTF3, TOX, RASF2, POU6F, UBAP2, SNORD37 and GMIP ), the nervous system ( RTTN, NLGN1, NFIB, PCDH9, and PPFIBP1), adipogenesis and metabolism ( FAM120B, CPA6, TMPRSS15 and FFAR4), sarcomere maintenance ( NCKIPSD), collagen synthesis ( COL1A2 ) and mitochondrial function ( NDUFS6, NDUFA12, NDUFA13, TOMM40, and ATP13A1 ). Co-localised SNPs (r 2 >0.6, p<0.05) were in genes enriched for breast cancer and lipoprotein metabolism. SNPs in chromosomes 1, 3, 10, 15, 18, 19 and 22 were shown to be cis-eQTL in a number of tissues. Phenome-wide analysis showed NDUF6 was associated with Crohn's disease, while NCKIPDS4 and TOMM40 were associated with lipidaemia, metabolic and liver disease. Conclusion: Our GWAS of NAFLD replicated known SNPs and identified new potential loci with implications in diverse biological process. Analysis of larger number of individuals with MRI-PDFF will allow further validation of the associations identified and enable prioritisation for functional studies.